The worst journey in the world - Cherry-Garrard, Apsley, 1886-1959.; Wheeler, Sara. (London : Vintage Books, 2010)
The author relates his experiences as part of the team that set out from England in 1910 under the leadership of Robert Falcon Scott to explore the Antarctic and attempt to be the first to reach the South Pole.
Originally published: Worst journey in the world, Antarctic, 1910-1913. London : Constable and Co., 1922. With new introd.
Adult.
Adult
Keywords: Cherry-Garrard, Apsley, -- 1886-1959 -- Travel -- Antarctica; Scott, Robert Falcon, -- 1868-1912 -- Travel -- Antarctica; Cherry-Garrard, Apsley, -- 1886-1959 -- Travel; Scott, Robert Falcon, -- 1868-1912 -- Travel; Antarctica -- Discovery and exploration -- British; Antarctica -- Exploration